SEKOLAH ALAM RUMBAI, PEKANBARU (STUDI KASUS TENTANG PENDIDIKAN YANG MEMBEBASKAN) - Hafizah "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The emergence of the School of Nature is a positive reaction to the conservative education system which is considered to ignore the aspects of student character development. dehumanization is the concept used by Paulo Freire to describe this conservative education system.School of Nature as an alternative means in educational institutions to improve the existing education system.This study aims to determine the process of free socialization at SekolahAlamRumbai and to find out the background of parents sending their children to school at the AlamSchool.The location of this study is in the District of RumbaiKelurahanLembah Sari, PekanbaruCity.The design of this study is descriptive qualitative using observation, interview and documentation techniques for all activities in the SekolahAlamRumbai.The results of this study indicate that parents' backgrounds send their children to SekolahAlamRumbai because SekolahAlam does not only prioritize academic achievement but there are still many other education programs taught by facilitators, learning systems implemented by schools, and School of Nature as a means of forming children's character.The facilitator's teaching background in the School of Nature is because the facilitator does not have to be a teacher of education graduates, the same vision and mission as well as the learning system and curriculum.For the socialization process, SekolahAlam has activities that free students, namely the relationship between facilitators and students, freedom to choose teaching materials, make and agree on rules and penalties and evaluation of learning that is not too formal.Based on these results, the Nature School can be regarded as a free education school. Keywords: School of Nature, Education that Liberates